On optimal frame expansions for multiple description quantization - Chou, Philip A.; Mehrotra, Sanjeev; Chou, Philip A. (Int'l Symp. on Information Theory, 2000)
We study the problem of finding the optimal overcomplete (frame) expansion and bit allocation for multiple description quantization of a Gaussian signal at high rates over a lossy channel. We provide a general analysis for the problem and solve it for the case of a 3X2 frame expansion.